2015
DOI: 10.1007/s11769-015-0781-y
|View full text |Cite
|
Sign up to set email alerts
|

Urban green space, uneven development and accessibility: a case of Dalian's Xigang District

Abstract: This study examines the socio-spatial context of uneven development and the residential accessibility of green space in Dalian of Liaoning Province, China. The social fairness was analyzed with a community scale as the basis. We combined social scientific methods with a GIS method using a behavior accessibility model from the perspectives of fairness of urban green space allocation based on social geography, geographic information science, management science and many other related discipline theories. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 17 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…For quantity, studies in Chinese cities show more cases of inequity-high-SES people have higher quantities of green space than low-SES [75,76,78,81,93,95,98,99,102,104]-than equity [12,82] or mixed findings [45,74]. Studies in other Asian cities such as Sheikhupura, Pakistan [69], Tehran, Iran [71,84], and Hamadan, Iran [46] also found inequitable results for green space quantity.…”
Section: Results: Do Inequities In the Global South Vary Based On Geomentioning
confidence: 98%
“…For quantity, studies in Chinese cities show more cases of inequity-high-SES people have higher quantities of green space than low-SES [75,76,78,81,93,95,98,99,102,104]-than equity [12,82] or mixed findings [45,74]. Studies in other Asian cities such as Sheikhupura, Pakistan [69], Tehran, Iran [71,84], and Hamadan, Iran [46] also found inequitable results for green space quantity.…”
Section: Results: Do Inequities In the Global South Vary Based On Geomentioning
confidence: 98%
“…This finding is consistent with the conclusions of other studies. For instance, Wu et al (2018) [41] and Yang et al (2015) [42] showed that the peripheries of Chinese cities are mostly low-income residential areas and have less access to parks and green spaces. The nearest neighbor method reveals a tendency to the uneven spatial distribution of refugee parks and the results can be used to provide policy suggestions to the municipal government in order to optimize the layout of urban refugee parks.…”
Section: Discussionmentioning
confidence: 99%
“…On the social scale, on the one hand, the urbanization dominated by spatial production has changed the social and cultural landscape and improved people's living standards. On the other hand, it also causes the widening income gap between urban and rural regions, and frequent occurrence of social stratification and spatial injustice [51]. On the natural scale, people pay more attention to the living environment and air quality, and the increasing demands for leisure, vacation and recuperation, which force the urbanization to strengthen the environmental protection and ecological restoration [49,52].…”
Section: Methodsmentioning
confidence: 99%